Foreign trade operations of banking sectors in Bangladesh with special reference to Standard Bank Limited - Monjur, Syed Raihan (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2018.